2012
DOI: 10.1001/jama.2012.7342
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Guillain-Barré Syndrome Following H1N1 Influenza Vaccination in Quebec

Abstract: UILLAIN-BARRÉ SYNDROME (GBS) is a peripheral neuropathy with acute onset and is characterized, in its typical presentation, by rapidly developing motor weakness and areflexia. 1,2 The disease is thought to be autoimmune and triggered by a stimulus of external origin. 1,2 In 1976-1977, an unusually high rate of GBS was identified in the United States following the administration of inactivated "swine" influenza A(H1N1) vaccines. 3 In 2003, the Institute of Medicine (IOM) concluded that the evidence favored acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 17 publications
4
46
2
1
Order By: Relevance
“…This risk is consistent with the level of risk reported by others. Estimates from single-country studies ranged from 1.05 to 4.70, the majority of which reported statistically significant increased risk [23][24][25][26][27][28][29][30][31][32]. Estimates were lower in studies of adjuvanted vaccines (1.05-3.04) [25,31] than in non-adjuvanted vaccines (1.57-4.70) [26][27][28][29][30]32].…”
Section: Discussionmentioning
confidence: 98%
“…This risk is consistent with the level of risk reported by others. Estimates from single-country studies ranged from 1.05 to 4.70, the majority of which reported statistically significant increased risk [23][24][25][26][27][28][29][30][31][32]. Estimates were lower in studies of adjuvanted vaccines (1.05-3.04) [25,31] than in non-adjuvanted vaccines (1.57-4.70) [26][27][28][29][30]32].…”
Section: Discussionmentioning
confidence: 98%
“…A Canadian study showed a small but significant increase in the number of GBS cases after mass influenza vaccination in Quebec [21] and a study from Germany on the Pandemrix vaccine reported a statistically significant association between GBS and vaccination in a 5-42 days risk window [6]. Unlike other studies, an American study by Vellozzi et al [22] suggested a protective effect of influenza A (H1N1) vaccination.…”
Section: Comparison To the Literaturementioning
confidence: 97%
“…Previous studies on GBS following the 2009 pandemic were mainly based on case-centre designs (collaborations between various health centres) [3], records collected from selected hospitals [6,20,21], or a case-control design [14]. These studies are therefore prone to biases from selection of participants, the methods of collecting information and recall bias.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 2 more Smart Citations